Ethnic inequality and community activities in Indonesia - Christophe Muller (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
For the first time in Indonesia, we jointly analyse several economic statistics and ethnic diversity indicators at national and local levels. Nationally, we find very high levels of economic inequality, measured from household asset values or consumption expenditure. In contrast, the levels of ethnic diversity, while non-negligible, are much lower, whether they reflect fractionalization, polarization, or ethnic inequality based on individual living standards. All ethnic inequality indicators surged after the Asian economic crisis. Ethnic inequality based on education is much lower and decreasing. In panel data models, individual participation in community activities is found to be much determined by local patterns of ethnic diversity. Different dimensions of ethnic diversity generate distinct effects. Ethnic polarization stimulates participation in strategic activities. Instead, ethnic fragmentation and ethnic inequality depress most local activities. Finally, we provide tentative explanations of local ethnic inequality in regressions that show a mixed pattern of socioeconomic influences.
Keywords: D71; H42; I32; 330; community activities; ethnic diversity; inequality; Indonesia